IDENTIFIKASI LOGAM BERAT DI LAHAN PASCA TAMBANG TIMAH DI KEPULAUAN BANGKA BELITUNG - Asep Kurnia; Nendi Rohaendi (PPSDM Geominerba, 2022)
The Bangka Belitung Islands Province (Babel) is one of the largest tin producing regions in Indonesia. The aim of the study was to identify the status and distribution of heavy metals (Pb, Cd, Cr, Zn, Mn) in post-mining areas in the Bangka Belitung Islands Province. This experiment was carried out through 3 stages of activity, namely: (1) Sampling of soil, water and plants in the field, (2) Analysis of heavy metal content in soil, water and plants as well as other soil chemical characteristics in the laboratory, and (3) Preparation of maps status and distribution of heavy metals in soil, water and plants in Kep Province. Bangka Belitung. Distribution of heavy metals Pb, Mn, Zn, and Cr in the soil is not normally distributed, while metal Cd is normally distributed, and the spatial distribution of metals Pb, Mn and Zn is distributed in groups, while metals Cd and Cr are evenly distributed. The frequency of detection of Cd exceeding the MAC value reached 96% spread over four districts). There is a very significant positive correlation (p<0.01) between Pb and Mn and Zn in the soil, and a significant negative correlation (p<0.05) between pH and Cr. The post-tin mining lands on Bangka Island covering an area of 56,421 ha generally have moderate to low levels of Pb, moderate to moderate Cd, moderate Cr, low to moderate Zn and low to moderate Mn. Heavy metals Pb, Cd, Mn, Zn and Cr were detected in all locations (n = 31), with minimum concentrations of 1.08 respectively; 0.79; 5.53; 42.01 and 0.65 mg/kg and the maximum is 76.05 respectively; 7.39; 560.66; 457.07; and 2.80 mg/kg. The detected frequency of Pb metal whose concentration exceeds the maximum allowable concentration (MAC) was 2 locations (8%), Cd metal 24 (96%), and Zn metal 8 locations (32%).